Employment as a journey or a destination? Interpreting graduates’ and employers’ perceptions – a Malaysia case study - Cheong, Kee Cheok; Hill, Christopher; Leong, Yin Ching; Zhang, Chen (Taylor & Francis, 2018)
As human capital came to the fore in the discourse on economic growth, so too has the concepts of employment prospects and employability attributes as students transit to the labor market. This paper examines three issues in this transition in the context of Malaysia. These are, first, how important is employment prospects a consideration when students choose institutions to join and programs to pursue? Second, what is their understanding of the attributes needed for employability? Third, how well do students’ understanding of both concepts accord with how employers understand them? Using a combination of survey and face-to-face interviews, this study confirmed the considerable importance of both concepts in students’ study decisions. Their understanding was broadly congruent with that of employers. These findings have implications for students’ learning experiences, for the education system, and for policy-makers hoping for the human capital needed to make the leap from a middle-income to a high-income nation.